ASSOCIATION OF IL-1Β AND IFN-Γ AND SUCCESSFUL PREGNANCY IN WOMEN UNDERGOING IN VITRO FERTILIZATION PROCEDURE - Safarova, A.F. (World of Medicine and Biology, 2023)
In this study, we aimed to investigate the association between immunological markers and a successful pregnancy following an in vitro fertilization procedure. A total of 131 patients were included in the study. They were grouped based on the outcome or parameters of the in vitro fertilization procedure such as successful pregnancy and female infertility. CD3, CD4, CD8, CD19, CD16/56 in the serum and cytokines in the serum and follicular aspiration fluid obtained during the process of oocyte pick-up were measured. There was no significant difference in CD3, CD4, CD8, CD19, CD16/56 levels in patients based on pregnancy outcome. IL-1β and IFN-y measurements were different in serum of patients with pregnancy and without pregnancy (p=0.041 and p=0.037, respectively). IL-1β levels were also different in the follicular aspiration fluid of patients with pregnancy and without pregnancy (p=0.039). Our study suggests an association between some cytokines (IL-1β in serum and follicular liquid) and IFN-γ (in serum)) and successful pregnancy in in vitro fertilization procedure.